2H/4H-Chromenes—A Versatile Biologically Attractive Scaffold - Raj, Vinit; Lee, Jintae (Frontiers in Chemistry, 2020)
2H/4H-chromene (2H/4H-ch) is an important class of heterocyclic compound with versatile biological profiles. This paper reports diverse synthetic strategies, synthetic mechanism, biological profiles, and structure-activity relationships regarding the bioactive heterocycle, 2H/4H-chromenes. Researchers discovered several routes for the synthesis of a variety of 2H/4H-ch analogs that exhibited unusual activities by multiple mechanisms. The direct assessment of activities with the parent 2H/4H-ch derivative enables an orderly analysis of the structure-activity relationship (SAR) among the series. In addition to 2H/4H-ch offering numerous exciting biological activities, such as anticancer, anticonvulsant, antimicrobial, anti-cholinesterase, and antidiabetic activities, previous approaches suggest that 2H/4H-ch, has excellent capability to regulate different types of cancer. The work on the present scaffold compiled in this article will help the scientific community design future work based on the 2H/4H-ch ring.